Efektivitas Pembelajaran Matematika dengan Strategi Pembelajaran Aktif Index Card Match (ICM) - St. Syahdan; Abdul Arif (Program Studi Pendidikan Matematika IKIP PGRI Jember, 2019)
This research is an experimental research which aim to know whether the active learning strategy index card match is more effective than expository learning strategy used learning mathematic for students in class VII State Islamic Junior High School at Pitumpanua, Wajo Regency. The design of the research used Posttest Control Group Design. In this research therean experimental group namely VIID class with 32 students which was taught using ICM active learning strategies and one groupcontrolnamely VIIE class with the same number students taught by expository learning strategy. Technique collection data used result of the learning tests, observation sheets for student activity, and questionnaire sheets for the student respond. Data analyzed used description statistic analyzed and statistic inferential analyzed. According to description statistic analyzed obtained:1) In the experimental group, the result of the mathematics learningobtained average of 74,16 with the deviation standard of 12.972 in the high criteria, while in the group control the average learning result of student amount 66,12 with the deviation standard 12,973 in the medium criteria. 2) Learning activities of students in the experimental group showed a positive attitude with a percentage of 58.04% and 51.45% in the control group. 3) The Student responses in the experimental learning group showed a positive response with percentage of 89.87% while in the control group 63.73%. Statistic inferential analyzed shows t count> t table (2.476> 1.67) with a significance of 5%, So we can conclude that the hypothesis is accepted it mean that learning mathematics in grade VII students of State Islamic Junior High School at Pitumpanua country of Wajo Regency through ICM active learning strategies is more effective than expository learning strategies